The Roces Family publishers : (with a history of the Philippines). (Philippines : Islas Filipinas Publishing Co., Inc., 1987)
There is a thin historical thread running through the fabric of the history of the Philippine press which identifies those who dedicated themselves to the honorable calling.
Roots in Spain -- A glimpse of Asturias -- Gijon : the Roces roots -- Three generations of publishers -- Don Alejandro Roces Sr. -- Don Ramon Roces y Pardo -- Sra. Elena Roces Guerrero -- Sra. Carmen Roces Davila -- A history of the Philippine press -- The First printing press -- The Early newspaper -- The Filipino press -- The Renacimiento Libel suit -- The English-language newspaper -- A new era begins -- The Weeklies -- The post-war publications -- The Press under Martial Law -- After EDSA --
Keywords: FAMILY -- PHILIPPINES; FAMILY CORPORATIONS -- PHILIPPINES; PRESS -- PHILIPPINES; ROCES FAMILY